Synthetic band-structure engineering in polariton crystals with non-Hermitian topological phases - L. Pickup (Nature Portfolio, 2020)
To simulate band structures of solid state materials synthetic lattices are usually generated by optical lattices or by irreversible patterning the system. Here, the authors present reconfigurable synthetic band-structures in optical exciton-polariton lattices and generate non-Hermitian topological phases.